The Hepatoprotective and Antioxidant Effects of Curcumin and NAcetylcysteine in Rats Exposed To Arsenic: hepatoprotective of Curcumin and NAC in arsenic-exposed rats - Fallah, Mostafa; Moghble, Najmeh; Javadi, Iraj; Shahriary, Alireza (Iranian Journal of Pharmaceutical Sciences, 2019)
Arsenic is a highly toxic element that is widely distributed in environment. Antioxidants depletion and oxidative stress is now considered as one of the possible mechanisms of arsenic-induced toxicity. Nacetylcysteine (NAC) and Curcumin (Cur) are potential antioxidants that can compensate the depletion of antioxidants. This study aimed to compare the hepatoprotective effect of Cur and NAC and their influences on total antioxidant capacity (TAC) in rats exposed to arsenic.The Rats were randomly divided into 6 groups, including control, G2 (arsenic), G3 (arsenic + NAC), G4 (arsenic + Cur), G5 (arsenic + NAC, post treatment) and G6 (arsenic + Cur, post treatment). Rats were exposed to 20mg/kg arsenic (by gavage) for 30 days and then treated with 300mg/kg NAC (by gavage) and 100mg/kg Cur (by gavage), individually. Serum level of TAC was measured using specific ELISA kits. Liver samples were collected for histopathological and morphological examinations. Arsenic treatment induced severe lesions and hepatocytes damages. Not only arsenic reduced significantly (p<0.001) the number of hepatocyte cells (27.83±1.47), but also it declined significantly (p<0.001) the mean of TAC value (0.4±0.1 μmol/l) in rats received arsenic alone. Treatment with NAC and Cur increased the mean of TAC value, enhanced the number of hepatocytes and reduced morphological damages of liver cells.NAC and Cur play important hepatoprotective roles against arsenic-induced toxicities by compensating cellular antioxidants. Therefore, NAC and Cur therapy can mitigate arsenic-induced toxicity, due to their anti-oxidative stress properties.